Prevention and Mitigation of Epidemics: Biodiversity Conservation and Confinement Policies - Emmanuelle Augeraud-Véron; Giorgio Fabbri; Katheline Schubert (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper presents a first model integrating the relation between biodiversity loss and zoonose pandemic risks in a general equilibrium dynamic economic set-up. The occurrence of pandemics is modeled as Poissonian leaps in economic variables. The planner can intervene in the economic and epidemiological dynamics in two ways: first (prevention), by deciding to preserve a greater quantity of biodiversity, thus decreasing the probability of a pandemic occurring, and second (mitigation), by reducing the death toll through a confinement policy. The class of social welfare functional considered has, as polar cases, a total utilitarian and an average utilitarian specifications. It implicitly considers, at the same time, the effects of policies on mortality and on the productive capacity of the country. Thanks to the Epstein-Zin specification of preferences, we disantangle risk aversion and fluctuation aversion. The model is explicitly solved and the optimal policy completely described. The qualitative dependence of the optimal policy on natural, productivity and preference parameters is discussed. In particular the optimal lockdown is shown to be more severe in societies valuing more human life, and the optimal biodiversity conservation is shown to be more relevant for more “forward looking” societies, with a small discount rate and a high degree of altruism towards individuals of future generations. We also show that societies accepting a large welfare loss to mitigate the pandemics are also societies doing a lot of prevention. After calibrating the model with Covid-19 pandemic data we compare the miti-gation efforts predicted by the model with those of the recent literature and we study the optimal prevention-mitigation policy mix.
Keywords: Q56; Q57; Q58; O13; C61; 330; biodiversity; Covid-19; prevention; mitigation; epidemics; Poisson processes; recursive preferences